Implementasi Pengelolaan Guru dan Tenaga Kependidikan dalam Peningkatan Kualitas pendidikan Berdasarkan IASP Tahun 2020 - Wahyuni, Femi Sri; Nugraha, Mulyawan Safwandy (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2024)
Implementation of strategic management is a necessity carried out by the school principal to carry out the school program as stated in the vision and mission, so that the planned school goals can be realized in a real and correct manner. Educational programs in madrasas, whether related to improving the quality of teacher resources, the quality of learning implementation or the quality of facilities and infrastructure, need to be improved to face global changes. If the quality of madrasah education is not improved through the management of teachers and education personnel, it is certain that madrasahs will lag further behind other levels of education of the same level. This research aims to find out the extent of the implementation of the management of teachers and education personnel in Improving the Quality of Education Based on the 2020 Educational Unit Accreditation Instrument (IASP) in MI, especially in MIN 2 West Bandung. In this research, researchers used a descriptive qualitative approach method. The data collection technique was carried out by means of observation, documentation study and of course interviews with the object of this research, namely the head of the madrasah.